The Role of Websites as Marketing Communication Media for Digital Startup Businesses in Companies Brainly - Cecep Teadi (Interkoneksi: Journal of Computer Science and Digital Business, 2023)
The use of information and communication technology is now constantly evolving and diversifying to suit the activities of modern and sophisticated humans. Website is one of the most popular media for promotion today. Website has unlimited reach of time and space. To obtain a website as an effective medium for conveying information, a certain strategy is needed so that the website promotion activities carried out achieve optimal results. One of the companies that uses a website as a digital marketing medium is Brainly, which focuses on its feature, namely “question and answer”. This study aims to find out how to use a website as a marketing communication medium with a case study on the Brainly website. This study uses descriptive research methods. Data obtained from documentation studies of the appearance of the Brainly website. The results of this study are in marketing media through the website showing that Brainly has six aspects of The 7C Framework, namely the aspects of context, content, community, communication, connection, and commerce.